2011
DOI: 10.1016/j.jpeds.2010.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Autoimmunity in Children with Type 1 Diabetes: A Two-Year Follow-Up

Abstract: Objective-To determine the benefits of screening for celiac autoimmunity via IgA transglutaminase autoantibodies (TG) in children with type 1 diabetes (T1D).Study design-We followed 79 screening-identified TG+ and 56 matched TG− children with T1D for 2 years to evaluate growth, bone mineral density, nutritional status, and diabetes control. TG+ subjects self-selected to gluten-free or gluten-containing diet.Results-Of the initial cohort, 80% were available for re-examination after 2 years. TG+ subjects had con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 34 publications
3
44
0
Order By: Relevance
“…The discordant findings among studies, the small numbers of patients, and the lack of distinction between symptomatic and asymptomatic patients make it difficult to comment on the real effect of adherence to a GFD in patients with T1DM. Recent studies suggest that no significant adverse outcomes take place in anti-tTG-positive children with T1DM who delay starting a GFD for 2 years (29) and that positive antibodies are insufficient to cause a noticeable effect on important outcomes (microvascular complications, neuropathy) for which coexisting enteropathy is required (30).…”
Section: Discussionmentioning
confidence: 99%
“…The discordant findings among studies, the small numbers of patients, and the lack of distinction between symptomatic and asymptomatic patients make it difficult to comment on the real effect of adherence to a GFD in patients with T1DM. Recent studies suggest that no significant adverse outcomes take place in anti-tTG-positive children with T1DM who delay starting a GFD for 2 years (29) and that positive antibodies are insufficient to cause a noticeable effect on important outcomes (microvascular complications, neuropathy) for which coexisting enteropathy is required (30).…”
Section: Discussionmentioning
confidence: 99%
“…Neither could the same intervention study, at a follow-up at the age of 8 years, indicate that delayed gluten introduction can decrease the risk of developing autoimmune T1D [119] . Also, in a 2-year prospectively followed cohort of subjects with already diagnosed T1D, with and without celiac autoimmunity, no significant adverse outcome was found in children with a delayed introduction of gluten [120] . Thus, there is still a controversial regarding the effect of gluten-free diet in T1D patients with celiac disease.…”
Section: Effect Of Gluten-free Dietmentioning
confidence: 92%
“…5,[32][33] In India, prevalence of celiac autoimmunity was reported to be 8%-22% among patients with established T1DM (Table 4). 24,[35][36][37][38][39][40] A two year follow-up study 41 was done at Barbara Davis Center for Childhood Diabetes to determine the impact of screening-detected celiac disease autoimmunity via IgA anti TTG antibodies in children with T1DM and GFD on growth, bone mineralization, and glycaemic control. It was found that anti TTG antibody positive subjects had consistently lower weight z-scores and higher urine N-telopeptides (a marker of bone turnover) than anti TTG antibody negative subjects, but had similar measures of bone densit y and diabet es outcomes.…”
Section: Coeliac Diseasementioning
confidence: 99%
“…Children who continued with high TTG index throughout the study had lower bone mineral density z-scores, serum ferritin and 25-hydroxy vitamin D, compared with the antibody negative group. 41 A study from university of Toronto compared CD associated with T1DM to CD alone. After following patients for 3 years it was found that CD associated with T1DM represents a distinct and a possibly milder form.…”
Section: Coeliac Diseasementioning
confidence: 99%